AN INVESTIGATION ON DIFFERENTIAL LEVELS OF GRIT AND COGNITIVE FAILURES AMONG THOSE DIAGNOSED WITH SUBSTANCE USE DISORDER AND NORMAL POPULATION - Edoka Anthony Chukwunonye, Ezenwa Micheal O , Okoli Paul Chibuike, Ugboma Cajetan Ikechukwu, Nwoye Callistus Chidiebere, Chime Peter Ekpunobi, Okpara Titus Chukwubuzo, Ofojebe Chukwuma Phiilip, Ozougwu Augustine Obumneme (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study investigated the difference in grit levels of those diagnosed with substance use disorder and normal population. A total of 52 in all, 26 from Enugu state neuropsychiatric centre (17 males and 9 females) and 26 students of Ihiala Nursing School (17 males and 9 females). The participants were selected using convenience sampling method. The ages of the participants ranged from 18 to 32. Two instruments used to gather data in the study were the Grit Scale and cognitive failure questionnaire. The study is a survey research; cross sectional design was adopted for the study; Multivariate Analysis of Variance was used in analysing the statistics. The findings show that The mean score of normal people in grit is 44. 46 while that of those diagnosed with substance use disorder is 35.42, showing that there is significant difference between normal people and those diagnosed with substance use disorder in grit. This implies that there is a significant difference in the grit levels of non addicts and addicts, (M= 44.46, 35.42, SD=3.74, 5.64) , p=.01. The second findings revealed that there is no difference in cognitive levels of non addicts and addicts, (M = 48.08, 47.56, SD =11.11, 15.53), p =.78. By the implication of this finding, it is recommended that clinicians in the management of substance use disorder, addicts can be taught and encouraged to be gritty. In so doing, they can cope with addiction treatment and avoid relapse. Besides, Clinicians should also devout more time in inculcating some of the positive behavioural characteristics in those who are suffering from substance use disorder. Finally, youths can as well be encouraged to imbibe positive behavioural characteristics which can help them exhibit some positive behaviours.